Association between discontinuation of benzodiazepine receptor agonists and post-operative delirium among inpatients with liaison intervention: A retrospective cohort study - Chie Omichi (Comprehensive Psychiatry, 2021)
Background: Several studies have investigated the association between benzodiazepine receptor agonist (BZDRA) use during the perioperative period and an elevated incidence of delirium. However, no study has focused on the time course of BZDRA use, including continuation, discontinuation, initiation, and no use. This study aimed to examine the influence of the time course of BZDRA use on post-operative delirium. Methods: This retrospective cohort study was conducted by reviewing medical records. We included patients who were scheduled for surgery under general anesthesia and had been referred to a liaison psychiatrist for pre-operative psychiatric assessment. The patients were classified into four groups based on the pre- and post-operative time course of oral BZDRA use, as follows: continuation, discontinuation, initiation, and no use (never used). The primary outcome was the prevalence of post-operative delirium in non-intensive care unit settings. We also performed stratified analyses according to age, the presence of cognitive impairment, the presence of delirium history, and antipsychotic drug use on admission. Results: Among 250 patients, 78 (31%) developed post-operative delirium. The Discontinuation group had a higher rate of delirium (49%, 24/49) than the other groups (Continuation [14%, 4/29]; Initiation [38%, 3/8], Never used [29%, 47/164], p = 0.008). Conclusions: Abrupt discontinuation of BZDRAs during the perioperative period may be a risk factor for post-operative delirium and should therefore be avoided.